2018
DOI: 10.1038/s41588-018-0166-0
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic loss of human CTNNA2, encoding αN-catenin, leads to ARP2/3 complex overactivity and disordered cortical neuronal migration

Abstract: Neuronal migration defects, including pachygyria, are among the most severe developmental brain defects in humans. Here, we identify biallelic truncating mutations in CTNNA2, encoding αN-catenin, in patients with a distinct recessive form of pachygyria. CTNNA2 was expressed in human cerebral cortex, and its loss in neurons led to defects in neurite stability and migration. The αN-catenin paralog, αE-catenin, acts as a switch regulating the balance between β-catenin and Arp2/3 actin filament activities. Loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 46 publications
2
62
0
Order By: Relevance
“…The activity of the branched actin nucleation machinery and tension-sensing factors are coordinated to ensure that actin remodeling is responsive to local forces generated within the epithelium. Biallelic mutations in the human αN-catenin gene CTNNA2 is causative for a recessive form of pachygyria (reduction in gyrus formation) (Schaffer et al, 2018). This study and an earlier biochemical study (Drees et al, 2005) revealed that in addition to its role in coupling linear actin to the cadherin complex, α-catenin is able to regulate branched actin polymerization by competing with Arp2/3 for G-actin binding in migrating pyramidal neurons.…”
Section: Branched Actin -The Epicenter Of the Junctional Cytoskeletonmentioning
confidence: 57%
“…The activity of the branched actin nucleation machinery and tension-sensing factors are coordinated to ensure that actin remodeling is responsive to local forces generated within the epithelium. Biallelic mutations in the human αN-catenin gene CTNNA2 is causative for a recessive form of pachygyria (reduction in gyrus formation) (Schaffer et al, 2018). This study and an earlier biochemical study (Drees et al, 2005) revealed that in addition to its role in coupling linear actin to the cadherin complex, α-catenin is able to regulate branched actin polymerization by competing with Arp2/3 for G-actin binding in migrating pyramidal neurons.…”
Section: Branched Actin -The Epicenter Of the Junctional Cytoskeletonmentioning
confidence: 57%
“…Furthermore, a recent study by Schaffer et al . highlighted the importance of Arp2/3 regulation in a human disorder known as pachygyria, where a mutation in CTNNA2 leads to an overactivity in Arp2/3, resulting in disordered cortical neuronal migration . Silencing Arp2 and Arp3 in Jurkat T cells results in failure to spread on anti‐CD3‐coated coverslips, switches the F‐actin‐rich lamellipodia leading edge to polarized filopodia‐like structures, which established the link between the β2‐integrin activation and functional Arp2/3 .…”
Section: Introductionmentioning
confidence: 99%
“…At 2 h, genes like catenin beta-2 (ctnnb2), serine/threonine-protein kinase ULK1 (ulk1), ephrin type-A receptor 8 (epha8), and gamma-aminobutyric acid receptor-associated protein (gabarap), associated with the generation of new neurites (Okazaki et al, 2000;Coyle et al, 2002;Gu et al, 2005;Lin et al, 2009), are highly suppressed. At 4 h the same pattern is observed, with suppression of genes like catenin alpha-2 (ctnna2; Schaffer et al, 2018), clathrin coat assembly protein AP180 (snap91; Bushlin et al, 2008), and protein furry homolog-like (fryl; Hayette et al, 2005). This contrasts with the late expression peak of neurite development genes like contactin-associated proteinlike 2 (cntnap2; Poliak et al, 1999), brain-specific angiogenesis inhibitor 1-associated protein 2 (baiap2; Kang et al, 2016), and protein furry homolog (fry; Hayette et al, 2005) at 24 h. These neuron projection development (GO:0031175) genes are also cytoskeletal modification genes.…”
Section: Structural Modificationmentioning
confidence: 58%